A pessoa religiosa consagrada hoje: uma investigação das experiências motivacionais - Oliveira, Helton Thyers Melo de (2024)
Amid the processes of subjectivation of contemporary culture and the transformations that traverse the institutional field of religion with the modern phenomenon of secularization, this work focused on problematizing the motivational experiences of religious men and women belonging to Catholicism, reflecting on the general panorama of the main motivations that presented themselves in the desire for consecration within the empirical field of Consecrated Religious Life (CRL). To investigate the subjective mobilizations of entry, development, and permanence in this confessional lifestyle, a quantitative and qualitative methodological approach was developed alongside the religious phenomenon investigated under the epistemological key of the Sciences of Religion. This involved conducting bibliographic research, based on interdisciplinary hermeneutics, bringing into dialogue concepts from Bergerian Sociology of Religion, humanistic Psychology, and vocational Theology. The thirty participants underwent biocentric interpersonal dynamics, production of textmeanings, bilateral stimulation of experiences, application of thematic questionnaires, and composition of experiential narratives through in-depth interviews. Thus, the main meanings that can support critical reflections on consecrated religious life as a cultural field of meaning production in contemporary religious phenomena were described. Understood from the perspective of the intersection of the concepts of liminality and the secularization process, fifteen categories of motivational experiences were obtained, highlighting the presence of plurality and differentiation as elements of charismatic articulation between person, community, and culture. The research was partially funded by the Coordination for the Improvement of Higher Education Personnel (CAPES) through the grant of a scholarship